VD_FINDINFO Décision / 2016 / 264 vom 15. April 2016 - VD Tribunal cantonal (2016)
PREUVE ILLICITE, DÉFENSE NÉCESSAIRE, AVOCAT DE LA PREMIÈRE HEURE | 130 let. b CPP (CH), 131 CPP (CH), 141 al. 5 CPP (CH)